Bone cement and cemented fixation of implants : 40 years of clinical practice and prospective for the future - Pipino, Francesco (nakladatel není známý, 2001)
A collection of works that focus on bone cements, cementing techniques and fixation of implants. Intended for professional public.
Keywords: Prosthesis Implantation; implantace protézy; Bone Cements; cementování; Cementation; kostní cementy; chirurgie